A Case of Delayed Tension Pneumocephalus in a Patient Undergoing Facial Cosmetic Surgery - Lee, Shih-Yu; Sun, Kuo-Shao (Archives of Clinical and Medical Case Reports, 2022)
There has been a recognizable surge in cosmetic surgery in recent years, partly influenced by social media, and the easy accessibility to such medical procedures. As with all types of surgery, the risks of complications are real, and in this specific setting, they tend to occur in a younger age group. Here, we discuss a rare complication and subsequent presentation of tension pneumocephalus, following an episode of cardiac arrest in a 58 year old female, during elective cosmetic-facial surgery. Typically, pneumocephalus develops when there are skull or facial bone fractures, and presents characteristically with leakage of cerebrospinal fluid from the ears and/or nose. The absence of the typical clinical signs and the lack of a clinical history or radiologically evidence of skull or facial bone fractions, may result in a delayed diagnosis, permanent brain injury and death. Awareness of such an unusual complication is therefore crucial when considering any surgery to the head and face (including cosmetic surgery), or following prolonged resuscitative efforts, which may well develop days after the inciting event.